Avaliação in vitro da eficácia de extratos de plantas medicinais do Cerrado frente Staphylococcus aureos isolado de difetentes fontes de propriedades leiteiras - Nader, Talita T. [UNESP]; Coppede, Juliana S.; Amaral, L. A. [UNESP]; Fachin, Ana Lúcia; Ferreira, L. M. [UNESP]; Pereira, Ana Maria Soares [UNESP] (My University, 2010)
The objective of this study is to evaluate the potencial microbial activity in-vitro from the extract of some endemic plants from Cerrado such as Baccharis dracunculifolia, Cochlospermum regium, Croton antisyphiliticus, Eugenia dysenterica and Lippia sidoides, against the agent Staphylococcus aureus isolated from bovine mastitic milk, osteo from cow’s teat, milker equipament, nasal cavitites and milker’s gullet. The extracts were prepared from aerial parts as well as the reticular systems of plants using the solvents methanol, hexane and chloroform at a concentration of 10%. To evaluate the antimicrobial activity, the technique of microdilution in broth was used for determining the Minimal Inibitory Concentration (MIC) followed by the determination of Minimal Bactericidal Concentration (MBC). The extracts from Baccharis dracunculifolia and Croton antisyphiliticus, followed by extracts from Lippia sidoides, reported respectively, presented better inhibitory activity against the multiplication of the bacteria Staphylococcus aureus. Furthermore, the results demonstrate that the isolated strains from the milk and nasal cavities of the milker showed strong resistance against gentamicin, active agent commonly applied to combat mastitis bovine. However, there was sensitivity against extracts from the reported plants, reinforcing the importance of the medicinal plants as a therapeutic resource and its aplicability.

O presente estudo teve como objetivo avaliar o potencial de atividade antimicrobiana in vitro dos extratos de algumas plantas endêmicas do Cerrado tais como Baccharis dracunculifolia, Cochlospermum regium, Croton antisyphiliticus, Eugenia dysenterica e Lippia sidoides, frente ao agente Staphylococcus aureus isolado de leite mastítico, ósteo do teto da vaca, equipamento de ordenhadeira, fossas nasais e garganta do ordenhador. Os extratos foram preparados a partir das partes aéreas e sistema radicular das plantas utilizando os solventes metanol, hexano e clorofórmio na concentração de 10%. Para avaliação da atividade antimicrobiana foi aplicada a técnica de microdiluição em caldo para determinação da Concentração Inibitória Mínima (CIM) seguida da determinação da Concentração Bactericida Mínima (MBC). Os extratos de Baccharis dracunculifolia, Croton antisyphiliticus, seguido do extrato de Lippia sidoides, apresentaram, respectivamente, melhor atividade inibitória sobre a multiplicação da bactéria Staphylococcus aureus. Os resultados obtidos demonstraram, ainda, que as estirpes isoladas do leite e das fossas nasais do ordenhador foram resistentes a gentamicina, princípio ativo muito utilizado no combate à mastite bovina, porém sensíveis aos extratos das plantas referidas, reforçando a importância das plantas medicinais como recurso terapêutico e sua aplicabilidade.
In-vitro evaluation of extract of medicinal plants from cerrado against the staphylococcus aureus isolated from different origins on dairy farms
Keywords: Antimicrobial activity; Phytotherapy; Lippia; Baccharis; Croton; Atividade antimicrobiana; Fitoterapia; Lippia; Baccharis; Croton